Effects of various contraceptives on ovulation through the morphological study of the ovary - Bedoya Hevia, Mariano (2015)
We have studied the oxytocic effect cervical ripening and enhancing oxytocin to 17 -Beto Estradiol applied in amniotic cavity in 10 pregnant women aged 38 or 40 weeks gestation action. Obtaining increased uterine activity due to an increase in the intensity and frequency of the contractions, cervical ripening in 50% of cases and the large increase in uterine activity when small doses of oxytocin administered, thus demonstrating the enhancing effect of this hormone oxytocin.